Produção de quitosana por Mucor subtilíssimus por fermetação semi-sólida em meio alternativo e aplicação na remoção do corante azul de metileno - Alves, Maria Rosângela Calheiros (2013)
Chitosan is a natural polymer derived from deacetylation of chitin, derived from the cell wall of fungi and exoskeletons of crustaceans. Due to its chemical structure exhibits properties of chitosan great biotechnological importance with many applications in the environmental fields, agriculture, cosmetics, among others. To check chitosan production by micro-organism, studies were performed using the fungus Mucor subtilíssimus UCP / WFCC 1262 isolated from soil of the savanna of the state of Pernambuco, through full factorial design of 23, by solid state fermentation (FSS) using sweet potato (Ipomoea batatas L.) supplemented with corn steep liquor (industrial waste) and yeast extract, and the response variables biomass and chitosan. For biomass production testing 5 whose composition 3g sweet potato, 8ml milhocina, and not using yeast extract showed the best result with 13.32 g / L of biomass, chitosan and the center point with 120.96 g / 100g biomass with the following composition: 20 g sweet potatoes, 6ml of corn steep liquor, 0.1 ml of yeast extract. The characterization of chitosan showed a degree of deacetylation of 60%. Microbiological chitosan obtained was tested for its environmental capacity in the discoloration of catiônicao dye, methylene blue (MB), process used in the textile industry having variables such as pH, time and temperature. Results obtained with efficiencies discoloration of methylene blue adsorption of the chitosan showed that the pH 6 was more efficient in bleaching AM biosorption with 92.73% under the condition of 8.30 mg to 20 mg of adsorbent in solution PM aqueous, suggesting its use in bioremediation processes of textile effluents.